THE CURRENT STATE OF KOREAN LANGUAGE EDUCATION AND KOREAN TEACHER TRAINING COURSES IN KAZAKHSTAN AND GRADUATES’ EMPLOYMENT STRATEGIES (Focusing on the case of Al-Farabi Kazakh National University) (Journal of Oriental Studies, 2022)
Korean Studies in Kazakhstan received scholarships or support and benefits to study in Korea andwere able to make great progress in a short period of time. Of course, the role and contribution of theKazakhstan government, which opened the way for Korean Studies education at universities, legally andinstitutionally through education policy, is also absolutely important. However, despite this series ofachievements, Korean Studies have been receiving great attention and love from many Kazakhstanians,but the current legal status of Korean in elementary, middle and high schools does not extend to thesecond foreign language. Therefore, based on the development of Korean Studies for nearly 30 years, Ihave now developed a plan so that graduates who especially majored in “korean language” can work inelementary, middle, and high schools using their majors rather than simply in commercial workplaces.As an alternative, first, through continuous contact at the government level, efforts are made to adoptKorean as a second language, and based on this, a pedagogical curriculum and appropriate experts arerecruited. In addition, the Korean government should provide support for graduates and teachers em-ployed in the program, even for a certain period of time, and establish a system for joint managementof the program between Korean Education Center in Almaty and the Department of the Far East(KoreanStudies).Key words: Korean Studies, Korean Language, Al-Farabi Kazakh National University, Department ofthe Far East(Korean Studies), Korean Education Center in Almaty.